ANALISIS KEMAMPUAN LITERASI EKONOMI BERDASARKAN PEKERJAAN ORANG TUA MAHASISWA STAI DARUL ULUM KANDANGAN - Muliyadi; Norwilistini (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2023)
This research is undermined by the low literacy of economics, which is a problem for every individual, like buying without considering the needs of consumers. By increasing economic literacy in every individual in particular, students can improve towards increasingly rational economic literacy. As well as aiming to raise awareness about managing finance and realizing rational decision-making for economic well-being. This research used descriptive qualitative.The subjects of this research were students of the Sharia Economic Studies Program at STAI Darul Ulum Kandangan with different backgrounds and professions of parents. The results of the research showed that the literacy of economics students is capable. As for the order of the level of ability, that are private academic, honorary teacher, farm worker, unemployed, retired, private officer, or farmer. In this study, there are nine indicators of economic literacy that appear in students of Shariah Economics at STAI Darul Ulum Kandangan, namely, economic problems, markets and prices, supply and demand, the role of government, income distribution, comparative advantage, national income, inflation, as well as monetary and fiscal policy.